A Caenorhabditis elegans Model for Integrating the Functions of Neuropsychiatric Risk Genes Identifies Components Required for Normal Dendritic Morphology. Issue 5 (1st May 2020) - Aguirre-Chen, Cristina; Stec, Natalia; Ramos, Olivia Mendivil; Kim, Nuri; Kramer, Melissa; McCarthy, Shane; Gillis, Jesse; McCombie, W Richard; Hammell, Christopher M
Abstract: Analysis of patient-derived DNA samples has identified hundreds of variants that are likely involved in neuropsychiatric diseases such as autism spectrum disorder (ASD) and schizophrenia (SCZ). While these studies couple behavioral phenotypes to individual genotypes, the number and diversity of candidate genes implicated in these disorders highlights the fact that the mechanistic underpinnings of these disorders are largely unknown. Here, we describe a RNAi-based screening platform that uses C. elegans to screen candidate neuropsychiatric risk genes (NRGs) for roles in controlling dendritic arborization. To benchmark this approach, we queried published lists of NRGs whose variants in ASD and SCZ are predicted to result in complete or partial loss of gene function. We found that a significant fraction (>16%) of these candidate NRGs are essential for dendritic development. Furthermore, these gene sets are enriched for dendritic arbor phenotypes (>14 fold) when compared to control RNAi datasets of over 500 human orthologs. The diversity of PVD structural abnormalities observed in these assays suggests that the functions of diverse NRGs (encoding transcription factors, chromatin remodelers, molecular chaperones and cytoskeleton-related proteins) converge to regulate neuronal morphology and that individual NRGs may play distinct roles in dendritic branching. We also demonstrate that the experimental value of this platform by providing additional insights into the molecular frameworks of candidate NRGs. Specifically, we show that ANK2/UNC-44 function is directly integrated with known regulators of dendritic arborization and suggest that altering the dosage of ARID1B/LET-526 expression during development affects neuronal morphology without diminishing aspects of cell fate specification.